Isolation of arbuscular mycorrhizal spores from different plat roots and their surrounding environment - Yong, Bryan Chuan Wang (Universiti Malaysia Sarawak (UNIMAS), 2015)
The general potential benefits of AMF were well documented but there is a need to study the potential of indigenous AMF species in plants in Kota Samarahan, Sarawak. The objectives ofthis study were to isolate and characterize arbuscular mycorrhizal fungi (AMF) root colonization in Kota Samarahan, Sarawak. The sampling of soil and plant roots of bamboo, banana, coconut and sugarcane was carried out at Kota Samarahan. There were 5 genera ofAMF being identified such as Acaulospora, Glomus, Dentiscutata, Funneliformis and Rhizophagus from four different plant species. The genera Glomus and Acaulospora were found to be dominant genera in these four plant species. The AMF spore population enumerated from bamboo, banana, coconut and sugarcane plants were 3.167, 4.767, 2.700 and 2.300 per gram, respectively. The percentage of AMF root colonization in bamboo, banana, coconut and sugarcane plants were 10.00%, 3.33%, 23 .33% and 6.67%, respectively . . The soil pH ofbamboo, banana, coconut and sugarcane are 4.9, 4.2, 4.7, and 4.3 respectively. The soil texture ofsoil samples ofbamboo, banana, coconut and sugarcane are silt loam, sandy loam, silt loam and silt loam respectively. This study showed that there were low number of spore population and AMF root colonization in four different plant species. The soil pH and soil texture were found to be affecting the population of AMF as . well as root colonization.